Digitalno gospodarstvo : konferenčni zbornik / X. posvet Pravo in ekonomija, 1. december 2017, Maribor - Marina Bajić; Repas, Martina (2018)
Digital Economy: Conference Proceedings /  Xth Conference Law and Economics, 1st of December, 2017, Maribor. This book contains papers that deal with six important areas of law regarding digital economy. The first paper examines the effect upon definition of “consumer” in EU law of the judgment of the CJEU in Schrems v. Facebook. The second paper aims to define the concept of smart contracts and to highlight some legal dilemmas in this respect. The main challenges of new technologies in the field of employment law are covered by the fourth paper. The fifth paper examines rules on Internet intermediary liability for user-generated content, which are based on the distinction between mere conduit, caching and hosting. Opportunities of digitalisation in the field of insurance are analysed in the fifth paper, and finally, the last paper analyses the role of law in the informatization of various aspects of operations in the Slovenian public sector. Although the authors seek to encroach on different legal fields, they argue that the existing rules apply to a number of highlighted issues, while for some of them a quick response of the legislator and judiciary with an understanding of the peculiarities of the Internet environment will be needed.
Keywords: digital economy; informatization; Internet; smart contract; insurance; Internet intermediaries; consumer